Glyphosate—A love story. Ordinary thoughtlessness and response‐ability in industrial farming. (19th June 2020) - Müller, Birgit
Abstract: More than 8.6 billion kilograms of glyphosate have been used worldwide since the 1970s. Herbicide tolerant crops became the lynchpin of the technological revolution for large‐scale farming first in the United States and Canada, and now in Europe. Zero‐till farming, as a production scheme and a world view, is based on simplifications promoted by a handful of transnational corporations with the complicity of politicians looking for easy solutions for problems, such as climate change, erosion and the hunger in the world. At the same time, the massive use of glyphosate is branded as an endocrine disrupter, causing cancer, male sterility and infertility. It interferes with soil bacteria and acts on the equilibrium of soil fungi. Glyphosate resistant crops connect farmers to far away consumers ingesting the food they grow together with the traces of chemicals. Farmers intra‐act with the myriads of life‐forms of the soil eco‐system. How do they perceive the life in the soil, when they spray chemicals? The article explores the political dimensions of the agency of both humans and non‐humans to understand the effects of the modernizing project of zero‐till, as well as to identify spaces and scales of possibility from where alternatives can emerge.